Patterns and Drivers of Agricultural Biodiversity in South Asia: A preliminary overview of a regional dataset - Kamal, Mustafa; Faisal, Asif Al; Kafle, Krishna; Karki, Saral; Krupnik, Timothy J.; Urfels, Anton (International Maize and Wheat Improvement Center, 2022)
Food systems face multifaceted challenges ranging from inadequate supply of nutritious food products to a range of negative environmental impacts (Fable et al., 202; Rockstöm et al., 2020; Willet et al., 2019). Fuctional agricultural bidiversity has emerged as an important consideration that, if carefully managed, could help to improved food system outcomes through several pathways including production risk miigation, increased and diversified incomes and livelihoods, and potentially as a contributor to healthier diets (Gaitán-Cremaschi et al., 2018; Klerkx & Rose 2020). However, large-scale regional patterns and drivers of agricultural biodiversity in South Asia remain largely underexplored. To address this gap, TAFFSA is producing a regional agricultural biodiversity database that will support researchers and policy markers in better understanding diversification in the food system and the relationships between agrobiodiversity and key food system outcomes. The current dataset contains regional district-level production data from 2019-2022, depending on availability, and includes a dietary groupings of food groups. Preliminary results show that cereals are by far the largest food category, but also highlight spatial variation in the diversity of food production. Bangladesh, Pakistan, Northen and Eastern India, and Nepal appear to be more diverse and dedicate larger shares of cultivated land to cereals than Western and Central India. After fully harmonizing the data sources,this dataset will help to identify hotspots of agobiodiversity including diagnostics and drivers of diversification that can inform sustainable food system transitions.